Analysis of EBNA-1 and LMP-1 variants in diseases associated with EBV infection in Chinese children - Ai Junhong; Xie Zhengde; Liu Chunyan; Huang Zhizuo; Xu Junmei (Virology Journal, 2012)
Abstract Background In China, primary EBV infection occurs during childhood with seroprevalence reaching about 100% by 10 years of age. There are few studies on EBV variants in diseases associated with EBV infection in Chinese children. In this study, we investigated the diversity of the EBV genes (EBNA-1 and LMP-1) and the relationship between EBV variants and the clinical phenotypes in diseases associated with EBV infections in Chinese pediatric cases. Results The frequencies of EBV type I in the IM, HLH and HL samples were 98.4%, 100% and 95.8%, respectively. Three known EBNA-1 variants were identified, including V-val (all were V-val-v1 sub-variant), P-thr' and V-Leu (MT). The frequency of V-val-v1 was 98.6% in the IM samples, 100% in the HLH samples and 97.1% in the HL samples. There were no significant differences of the distribution of EBNA-1 variants between IM, HLH and HL samples (P > 0.05). Three known LMP-1 variants, including China 1, China 2 and Med, were identified and China 1 was predominant in all groups (IM 88.6%, HLH 100% and HL 100%). The frequency of del-LMP-1 was 88.6% in the IM samples, 100% in the HLH samples and 96.0% in the HL samples. There were no significant differences in the frequency of del-LMP-1 between the IM, HLH and HL samples (P > 0.05). The frequency of XhoI loss was 90.6% in the IM samples, 100% in the HLH samples and 100% in the HL samples, with no significant difference in frequency (P > 0.05). In the EBV type I strain, V-val-v1 variant (EBNA-1) was linked with China1 variant (LMP-1) in 88.9% of the IM samples, 100% of the HLH samples and 80.0% of the HL samples in this study. Conclusions Type I EBV was the most prevalent subtype EBV in Chinese pediatric cases and V-val-v1 (EBNA-1) and China1 (LMP-1) variants were the most dominant variants. There was a strong linkage between V-val-v1 (EBNA-1) variant and China1 (LMP-1) variant in type I EBV. The sequence variation in EBV genes may represent a geographic polymorphism since no preferential associations were found between specific EBV variants and specific diseases in this study.